Utilizing Waste Materials as Art Learning Media in Early Childhood Education - Erdaliameta, Annisha; Fitriana, Laila; Utami, Winda Sherly (Asian Journal of Early Childhood and Elementary Education, 2025)
This study examines the use of diverse media and gaming technologies to provide tangible learning experiences in early childhood education, focusing specifically on learning media made from residual waste. The use of residual waste as a learning medium is grounded in its accessibility in children’s everyday environments and its potential to teach recycling and waste reduction. Adopting a qualitative research method with a descriptive approach, this study aims to describe the use of residual waste as a medium for early childhood art learning. The research was conducted at TK Negeri 6 Yogyakarta with 15 participants comprising the principal, teachers, and group B2 children. Data were collected through observation, documentation, and interviews, and were analyzed using the Miles and Huberman model, which involves data reduction, data display, and conclusion drawing or verification. The findings show that the use of residual waste as a learning medium is organized into three stages: implementation, planning, and evaluation. The use of residual waste has proven to be effective in art learning for young children because, through such learning media, children are free to create according to their own creativity and imagination.